Feasibility of transdermal transport of atenolol by combination of iontophoresis and oleic acid pretreatment - Akhmad Kharis Nugroho; Arief Rahman Hakim; Marlyn Dian Laksitorini; Fajar Rakhmatullah; Eny Masruriati (Indonesian Journal of Pharmacy, 2011)
Atenolol  has  a  low  oral  bioavailability  and  a  short  elimination  half-life. Therefore,  alternative  route  and  delivery  system  is  important.  Transdermal iontophoresis,  i.e.  a  systemic  drug  delivery  via  the  skin,  implementing  a  low intensity  of  electrical  current,  is  one  attractive  candidate.  This  study  evalu ated feasibility  of  atenolol  transdermal  transport  when  iontophoresis  is  applied  after enhancer  pretreatment.  There  were  4  formulas  prepared;  2  implemented iontophoresis  for  3  hours  (current  density:  0.25  mA/cm2)  while  the  others  did not  use  iontophoresis.  The  enhancer  was  oleic  acid  (5  or  10%  as  a  mixture  in propylene  glycol)  with  duration  of  pretreatment  of  one  hour.  Transport  was evaluated  in  the  diffusion  studies  across  the  fresh  rat  skin  in  a  static-vertical diffusion system. Data were analyzed based on the numeric convolution method to  obtain  simulated  Cp  profiles  as  well  as  AUC  of  Cp  profiles.  Based  on  the simulated Cp, the best transport was achieved in Formula 3, where iontophoresis is  performed  across  the  skin,  pretreated  with  5%  oleic  acid  for  one   hour.  The value  of  simulated  Cp  indicated  achievement  of  therapeutics  level  of  atenolol, suggesting the feasibility of the atenolol delivery by iontophoresis.Key words : atenolol, transdermal, iontophoresis, enhancer